Peran Pendidikan Kewirausahaan, Pengembangan SDM Unggul, Inovasi Digital, dan Keberlanjutan dalam Mendorong Ekosistem Technopreneurship - Isnawati Osman; Abu Muna Almaududi Ausat; Risnawati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The background of this study is based on the increasing need to integrate entrepreneurial competencies with technology utilization in responding to the dynamics of the digital economy. This study aims to comprehensively examine the roles of entrepreneurship education, the development of high-quality human resources, digital innovation, and sustainability in supporting the technopreneurship ecosystem. The study employed a literature review method with a qualitative approach and descriptive analysis, using data sources from various scientific articles obtained through Google Scholar and other credible websites published between 1964 and 2026. From an initial search of 50 articles, a rigorous selection process resulted in 33 relevant articles used as the basis for analysis. The data analysis technique applied was descriptive qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that entrepreneurship education plays an important role in shaping innovative mindsets, the development of superior human resources enhances adaptive capacity and productivity, digital innovation accelerates business model transformation, and sustainability ensures a balance between economic growth and social-environmental responsibility. The integration of these four aspects has proven to create synergy that strengthens the competitiveness of technopreneurship. These findings highlight the importance of a holistic approach in developing a technology-based entrepreneurial ecosystem that is more adaptive, innovative, and sustainable.